Application Of Hiding Messages With Cryptographic Algorithm Modification of Caesar Cipher and Hill Cipher - Rini Wijayanti; Siska Febriani; Dony Ariyus (CCIT Journal, 2020)
In the current of information technology, we need a way to properly secure message. Message seurity aims to avoid intruders in communication, because the messages sent are confidential. Which can only be accessed by people who have interests. One way to secure messages is by the cryptographic method. There are many cryptograpic algorithms that can be used, such as Caesar Cipher and Hill Cipher. Both of these algorithms are symetric group cryptographic algorithms, because the keys used in the encryption and decryption process use the same key. To provide a double level security, both algorithm modifications were made. Caesar Cipher carried out the conversion process into binary numbers, and carried out XOR operations by shifting keys as an encryption process. Whereas in the Hill Cipher modification is done by using some Regional Bank codes as a key for message encryption and decryption process. The final process to get the ciphertext end result is to do permutations with a modified formula, which is adjusted to needs. The result of this study are a combination of algorithmsthat can be used to secure messages sent tp recipients. The testing process is done by comparing the size of the original image file used with the size of the resulting file size and the number of characters that can be accommodated.